Regional Economic Outlook, October 2009, Asia and Pacific : Building a Sustained Recovery. (Regional Economic Outlook, 2009)
Asia has rebounded fast from the depth of the global crisis. Initially, the region was hit extremely hard, with output in most countries shrinking by much more than even those nations at the epicenter of the crisis. But starting in February 2009, Asia's economy began to revive. Exports and industrial production have increased again, financial pressures have eased, confidence has largely been restored. What explains this remarkable comeback? What challenges does the recovery pose to Asian policymakers? These are the main questions addressed in the IMF's October 2009 "Regional Economic Outlook: Asia and Pacific." The report discusses the latest developments in Asia, examines the prospects for the period ahead, and considers the policy steps needed to sustain the recovery and rebalance Asia's medium-term growth. Published biannually in May and October.